Comparative familial aggregation of bipolar disorder in patients with bipolar I and bipolar II disorders. (August 2018) - Parker, Gordon B; Romano, Mia; Graham, Rebecca K; Ricciardi, Tahlia
Objective: We sought to quantify the prevalence and differential prevalence of a bipolar disorder among family members of patients with a bipolar I or II disorder. Methods: The sample comprised 1165 bipolar and 1041 unipolar patients, with the former then sub-typed as having either a bipolar I or II condition. Family history data was obtained via an online self-report tool. Results: Prevalence of a family member having a bipolar disorder (of either sub-type) was distinctive (36.8%). Patients with a bipolar I disorder reported a slightly higher family history (41.2%) compared to patients with a bipolar II disorder (36.3%), and with both significantly higher than the rate of bipolar disorder in family members of unipolar depressed patients (18.5%). Conclusions: Findings support the view that bipolar disorder is heritable. The comparable rates in the two bipolar sub-types support the positioning of bipolar II disorder as a valid condition with strong genetic underpinnings.